Need Analysis for Choosing English Teaching Concepts at IPDN - Layla Kurniawati; Edi Wahyono (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
English is a subject that given in the three curriculum systems at IPDN has not been implemented maximally. The three existing curriculum systems provide almost the same material and there are not clear and obvious differences. In order to improve the teaching conditions, need analysis is used to find and determine what English learning materials are appropriate and suitable for teaching and learning at IPDN. A descriptive qualitative approach through document study, interview, and observation was used in this research. From the analysis, teaching English must be developed with the collaborative approach among education personnel (lecturers, trainers, fellows) and students in the three curriculum systems at IPDN. English teaching emphasizes reading skills, where teaching reading focuses on English for Specific Purposes of Government administration as core knowledge.